2017
DOI: 10.1177/0269215517715762
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation improves exercise tolerance in patients with advanced heart failure on continuous intravenous inotropic support use—randomized controlled trial

Abstract: A short-term inpatient neuromuscular electrical stimulation rehabilitation protocol improved exercise tolerance and reduced intravenous inotropic support necessity in patients with advanced heart failure suffering a decompensation episode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…Because the purpose of our study was to determine the ability of the NMES to influence the concentration of HbA 1C , lipid profiles, and hemodynamic parameters in T2DM patients, we used 35-Hz NMES eliciting incomplete, tetanic contractions of the muscles. NMES frequencies between 10 and 50 Hz (eliciting tetanic contractions) proved effective in our earlier study [26] and in the randomized clinical trials with patients with chronic cardiac deficiency conducted by other authors [27][28][29][30][31][32][33][34][35][36][37]. The authors of the studies who applied NMES for 3-12 weeks reported that it improved participants' exercise capacity [26,[28][29][30][31][32]34,36,37], metabolic and hemodynamic parameters, including peak VO 2 [28][29][30][31]34,37], as well as reducing their diastolic blood pressure [29], and increasing LVEF (%) [26].…”
Section: Interventionsmentioning
confidence: 63%
“…Because the purpose of our study was to determine the ability of the NMES to influence the concentration of HbA 1C , lipid profiles, and hemodynamic parameters in T2DM patients, we used 35-Hz NMES eliciting incomplete, tetanic contractions of the muscles. NMES frequencies between 10 and 50 Hz (eliciting tetanic contractions) proved effective in our earlier study [26] and in the randomized clinical trials with patients with chronic cardiac deficiency conducted by other authors [27][28][29][30][31][32][33][34][35][36][37]. The authors of the studies who applied NMES for 3-12 weeks reported that it improved participants' exercise capacity [26,[28][29][30][31][32]34,36,37], metabolic and hemodynamic parameters, including peak VO 2 [28][29][30][31]34,37], as well as reducing their diastolic blood pressure [29], and increasing LVEF (%) [26].…”
Section: Interventionsmentioning
confidence: 63%
“…12 EMS is a novel intervention that shows beneficial effects on both physical function and exercise capacity. [14][15][16][17][18] Therefore, we postulated that EMS therapy would be effective in frail elderly AHF patients. In contrast, EMS therapy has some potential to adversely affect the patients.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary for AHF patients to achieve and maintain optimal physical function, and exercise therapy is required to maintain physical function in HF patients, especially in frail elderly subjects . EMS is a novel intervention that shows beneficial effects on both physical function and exercise capacity . Therefore, we postulated that EMS therapy would be effective in frail elderly AHF patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several reports demonstrated the efficacy of EMS in patients with advanced HF. 62 , 63 For instance, Forestieri et al 64 demonstrated the improvement of exercise capacity in patients by EMS, and EMS demonstrated a significantly higher dose reduction in dobutamine infusion. By contrast, the addition of inspiratory muscle training was reported to improve quality of life in patients with HF.…”
Section: Methodology Of Exercise Training In Patients With Advanced Hmentioning
confidence: 99%